2013
DOI: 10.1007/s00381-013-2286-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscope-assisted repair of metopic synostosis

Abstract: Endoscope-assisted repair of metopic synostosis is safe and offers promising results in infants before the age of 6 months. Molding helmet therapy following surgery is very important in obtaining the good results. Early diagnosis and referral for surgery are crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…4,32 The purpose of this work was to ascertain the incidence of intra- and postoperative complications in a single center. Although a number of studies have reported on various metrics of success in endoscopic 10,13,15 or open 9,28 craniosynostosis surgeries, few have directly compared results of the two on a large cohort of patients. 6,17 We present a retrospective study examining complications after surgery in non-syndromic and syndromic cases of craniosynostosis.…”
Section: Introductionmentioning
confidence: 99%
“…4,32 The purpose of this work was to ascertain the incidence of intra- and postoperative complications in a single center. Although a number of studies have reported on various metrics of success in endoscopic 10,13,15 or open 9,28 craniosynostosis surgeries, few have directly compared results of the two on a large cohort of patients. 6,17 We present a retrospective study examining complications after surgery in non-syndromic and syndromic cases of craniosynostosis.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this troublesome disparity, we suggest that there remains insufficient clinical evidence to summarily declare that endoscopic strip craniectomy is ''safe'' with ''minimal'' risks. 23,25,26,29 One notable limitation of the endoscopic approach is the complete dependence on strict postoperative helmet therapy, which typically lasts for 6 to 9 months or longer. 26,30 Conceptually, helmet therapy facilitates an optimal head shape by directing the growth of the brain and calvarium after excision of the synostosed suture.…”
Section: Discussionmentioning
confidence: 99%
“…Different methods have been attempted in order to decrease blood loss and to prevent transfusion complications. Even though there have been many efforts to improve blood sparing during craniosynostosis surgery, including minimally invasive and endoscopic techniques (6,10,12,14), the use of autologous blood obtained from the patient in the preoperative period (11), intraoperative aminocaproic acid (17), tranexamic acid (4,8), preoperative recombinant human erythropoietin (15) and fibrin glue (25) applications, there is no concise or universally accepted procedure yet.…”
Section: █ Discussionmentioning
confidence: 99%